Accidental Coverage of Both Renal Arteries during Infrarenal Aortic Stent-Graft Implantation: Cause and Treatment - Umberto Marcello Bracale; Anna Maria Giribono; Gaetano Vitale; Donatella Narese; Gianpaolo Santini; Luca del Guercio (Case Reports in Vascular Medicine)
The purpose of this paper is to report a salvage maneuver for accidental coverage of both renal arteries during endovascular aneurysm repair (EVAR) of an infrarenal abdominal aortic aneurysm (AAA). A 72-year-old female with a 6 cm infrarenal abdominal aortic aneurysm was treated by endovascular means with a standard bifurcated graft. Upon completing an angiogram, both renal arteries were found to be accidentally occluded. Through a left percutaneous brachial approach, the right renal artery was catheterized and a chimney stent was deployed; however this was not possible for the left renal artery. A retroperitoneal surgical approach was therefore carried out with a retrograde chimney stent implanted to restore blood flow. After three months, both renal arteries were patent and renal function was not different from the baseline. Both endovascular with percutaneous access via the brachial artery and open retroperitoneal approaches with retrograde catheterization are feasible rescue techniques to recanalize the accidentally occluded renal arteries during EVAR.